The Effects of Dysmenorrhea to Lifestyle: A Case Study on Female Students in Malaysia - Chong, Teek Foh; Ser, Xin Ee; Ooi, Lay Khuan; Wong, Ling Shing (INTI International University, 2019)
A survey was carried out in 2017, to analyze the occurrence of dysmenorrhea among female students. A cross-sectional descriptive study was conducted on 201 female subjects, with the questionnaire contained the general information of the participants and questions related to menstruation. The survey were conducted through face-to-face and online approaches. The results indicated that the occurrence of dysmenorrhea among female students was 80 %, with majority of them had biased body constitution. The top three biased constitutions in the dysmenorrhea group were qi deficiency constitution, qi stagnation constitution and yin deficiency constitution. The main trigger factors to the occurrence of dysmenorrhea and causing the severity of dysmenorrhea were the stress and dietary biased.